Photoinduced electron-transfer α-deoxygenation of aldonolactones. Efficient synthesis of 2-deoxy-d-arabino-hexono-1,4-lactone - Bordoni, Andrea Veronica (2006)
A photoinduced electron-transfer (PET) reaction was used for the deoxygenation at C-2 of aldonolactones derivatized as 2-O-[3-(trifluoromethyl)benzoyl] or benzoyl esters. By irradiation of different D-galactono- and D-glucono-1,4-derivatives, with a 450 W lamp, using 9-methylcarbazole as photosensitizer, the corresponding 2-deoxy-D-lyxo- and 2-deoxy-D-arabino-hexono-1,4-lactones were efficiently obtained.O-[3-(trifluoromethyl)benzoyl] or benzoyl esters. By irradiation of different D-galactono- and D-glucono-1,4-derivatives, with a 450 W lamp, using 9-methylcarbazole as photosensitizer, the corresponding 2-deoxy-D-lyxo- and 2-deoxy-D-arabino-hexono-1,4-lactones were efficiently obtained.D-lyxo- and 2-deoxy-D-arabino-hexono-1,4-lactones were efficiently obtained.